Testing the Antecedents of Attitudes towards Organic Food (An Extended of the Theory of Planned Behaviour) - Sitaniapessy, Arthur; Sitaniapessy, Harry Anthony Pierre; Sutrasmawati, Endang (Department of Management, Faculty of Economics and Business, Universitas Negeri Semarang, 2023)
The primary purpose of this study was to examine purchase intention and behavior of organic food based on the theory of planned behavior. People do not always use their intentions to behave even though intentions are powerful. The novelty of this study is to add two antecedent variables of attitude, namely knowledge about organic food and attention to health. The sampling technique used was purposive sampling. This research was conducted through two studies. Study I was conducted to test the extent of TPB, and Study II tested buying behavior. The sample size is 187 respondents for Study I and 153 respondents for Study II. Data were analyzed using Structural Equation Modeling (SEM) for Study I and Logistic Regression for Study II. The study results show that the overall hypothesis proposed is supported and that intention has a substantial impact on buying behavior of organic food. Based on this research, producers or marketers can develop better marketing strategy models to increase consumer understanding of the benefits of organic food consumption.